Exploring the factors affecting academic performance: A path analysis of english proficiency, code switching and code mixing among TARUMT students - Ting Tin Tin; Wong Yi Cheng; Yap Tee Jin; Chaw Jun Kit; Wan Nor Al-Ashekin Wan Husin; Ali Aitizaz; Lee Kuok Tiung; Ayodeji Olalekan Salau; Umar Farooq Khattak; Yasin Ahmed Siddiqui (Scopus, 2024)
Addressing the gap between potential and achievement in Malaysia's education system is important for the nation’s development. Despite Malaysia's progress as a developing country, Malaysia continues to face challenges in education. In comparison to other developing countries, it is apparent that Malaysia lags behind international averages. This study seeks to understand the various factors (parental involvement, selfesteem, level of introversion and level of extroversion) influencing TARUMT students' academic performance, focusing particularly on the mediating roles of English language proficiency, code switching and code mixing. An online questionnaire was utilized to gather data from TARUMT students and a total of 100 responses were collected. Cronbach’s alpha was used to measure the questionnaire items’ reliability, whereas Pearson correlation and path analysis model was used in data analysis. The results suggested that there is a significant positive effect of parental involvement on English language proficiency. However, English proficiency did not mediate the relationships between parental involvement and code switching or code mixing, nor did it significantly affect overall academic performance. Similarly, no significant effects were found between selfesteem, introversion and extroversion on English proficiency or academic achievements. Moreover, English proficiency, code switching or code mixing showed no significant mediating effect on self-esteem, personality traits (level of introversion and level of extroversion) and academic performance. The study suggests that while parental involvement enhances English skills, it does not translate into academic achievement. These findings offer insights for policymakers aiming to reform Malaysia's education system in efforts to address its stagnation.